Proposition an Algorithm for segmentation an Ambiguous text of Arabic - touati tliba, mohammed; atia, djaber (جامعة الوادي University of Eloued, 2019)
"شهدت انظمة التعرف على الكتابة ( )OCR: Optic Character Recognitionتطورا كبيرا في العديد من المجالات مثل: التعرف على محتوى الصكوك البنكية, تحويل الملفات المطبوعة الى نصوص قابلة للتعديل بالآلة. اعطت العديد من البحوث المنجزة في مجال التعرف على الخط نتائج جيدة جدا خاصة اللغات اللاتينية,ولكن بالرغم من ذلك مزالت تعاني من نقائص كثيرة في مجال التعرف على الخط العربي وخاصة المكتوب بخط اليد بسبب طريقة الكتابة والإلتصاق والتقاطع بين الأحرف. قمنا بتقديم دراسة عامة حول انظمة التعرف على الخط العربي, ثم تطرقنا الى مرحلة مهمة وهي تقسيم الكلمات ,حيث تطرقنا الى مختلف المشاكل التي تواجه تقسيم الخط العربي بعدها شرحنا مختلف الطرق المستعملة للتقسيم ,ثم خطوات التقسيم. في هذا العمل , قمنا بطرح خوارزمتين تعتمد على البحث عن نقاط الاهمية لتجزئة الكلمة ,حيث الخوارزمية الاولى تعمل على استخراج مشكل التقاطع بين الحروف والخوارزمية الثانية تعمل على التقسيم الافقي للكلمات المكتوبة بشكل عمودي. قمنا بتجريب العمل المطروح على عينة من الصور المكتوبة بخط اليد العربي ,وكانت النتائج جيدة ومشجعة جدا.""OCR: Optic Character Recognition has developed in many areas such as: recognition of the contents of bank instruments, conversion of printed files into adaptable texts. Many of the research done in the field of handwriting recognition has produced very good results especially in Latin languages. However, there are many shortcomings in the field of handwriting recognition, especially in handwriting, because of the way of writing, sticking and intersecting letters. We presented a general study on the systems of recognition of the Arabic calligraphy, and then we addressed the important stage of the division of words, where we addressed the various problems facing the division of Arabic calligraphy then explained the different methods used for division, and then division. In this work, we have introduced two algorithms based on the search for the points of importance of word segmentation, where the first algorithm works to extract the problem of the intersection of letters and the second algorithm works on the horizontal division of words written vertically. We tried the work on a sample of pictures in Arabic handwriting, and the results were very good and encouraging."
mémouer master informatigue
Keywords: التعرف على الكتابة , كتابة اليد , التجزئة , PAW.; OCR, segmentation, Arabic Characters, PAW